Intradiscal Injection of Induced Pluripotent Stem Cell-Derived Nucleus Pulposus-Like Cell-Seeded Polymeric Microspheres Promotes Rat Disc Regeneration - Kaishun Xia; Jian Zhu; Jianming Hua; Zhe Gong; Chao Yu; Xiaopeng Zhou; Jingkai Wang; Xianpeng Huang; Wei Yu; Liming Li; Jianqing Gao; Qixin Chen; et al. (Hindawi Limited, 2019)
Background. Cell replacement therapy is an attractive alternative for treating degenerated intervertebral discs (IVDs), which are related to the reduction of nucleus pulposus-like cells (NP-lCs) and the loss of the extracellular matrix. Induced pluripotent stem cells (iPSCs) which resemble embryonic stem cells are considered to be a potential resource for restoring NP-lCs and disc homeostasis. Here, we proposed an efficient two-step differentiation protocol of human iPSCs into NP-lCs and continuously tested their in vivo ability to regenerate IVDs. Methods. A polymeric gelatin microsphere (GM) was generated for sustained release of growth and differentiation factor-5 (GDF-5) and as a cell delivery vehicle of NP-lCs. By injecting NP-lC-seeded GDF-5-loaded GMs into the rat coccygeal intervertebral discs, the disc height and water content were examined with the molybdenum target radiographic imaging test and magnetic resonance imaging examination. Histology and immunohistochemistry results were shown with H&E, S-O-Fast Green, and immunohistochemistry staining. Results. We demonstrated that the injection of NP-lC-seeded GDF-5-loaded GMs could reverse IDD in a rat model. The imaging examination indicated that disc height recovered and water content increased. Histology and immunohistochemistry results indicated that the NP cells as well as their extracellular matrix were partially restored. Conclusions. The results suggest that NP-lC-seeded GDF-5-loaded GMs could partially regenerate degenerated intervertebral discs after transplantation into rat coccygeal intervertebral discs. Our study will help develop a promising method of stem cell-based therapy for IDD.